Meningkatkan Keterampilan Memakai Sepatu Bertali Melalui Model Direct Instruction pada Anak Disabilitas Intelektual Sedang (Single Subject Research Kelas VIII di SLB Yappat Lubuk Sikaping) - Putri, Refa Julianti; Zulmiyetri, Zulmiyetri; Iswari, Mega; Budi, Setia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to Improving Shoelace Skills Through Direct Instruction in Children with Moderate Intellectual Disabilities in Grade VIII at SLB YAPPAT Lubuk Sikaping. This research was motivated by a problem the researcher encountered at the YAPPAT Special Needs School in Lubuk Sikaping. A child with a moderate intellectual disability was unable to lace up shoes independently. This study aimed to improve shoelace skills through direct instruction. This study used a quantitative approach with an experimental approach in the form of Single Subject Research (SSR) using an A-B design. The data collection technique used was an action test. The data analysis technique in this A-B design SSR research involves several stages. The subjects were eighth-grade children with moderate intellectual disabilities at the YAPPAT Special Needs School in Lubuk Sikaping. The results showed that in the baseline condition (A1), which was conducted in three sessions, a stable percentage of 37.5% was achieved, and in the intervention condition (B), which was conducted in 11 sessions, a stable percentage of 93.75%. Based on the research results, it can be concluded that the direct instruction model can improve lace-up shoe-wearing skills in children with moderate intellectual disabilities.